Direction of chromosome rearrangements in Saccharomyces cerevisiae by use of his3 recombinational substrates. - Fasullo, M T (1988)
We used the his3 recombinational substrates (his3 fragments) to direct large interchromosomal (translocations) and intrachromosomal (deletions and tandem duplications) rearrangements in the yeast Saccharomyces cerevisiae. In strains completely deleted for the wild-type HIS3 gene, his3 fragments, one containing a deletion of 5' amino acid coding sequences and the other containing a deletion of 3' amino acid coding sequences, were first placed at preselected sites by homologous recombination. His+ revertants that arose via spontaneous mitotic recombination between the two his3 fragments were selected. This strategy was used to direct rearrangements in both RAD52+ and rad52 mutant strains. Translocations occurred in the RAD52+ genetic background and were characterized by orthogonal field alternating gel electrophoresis of yeast chromosomal DNA and by standard genetic techniques. An unexpected translocation was also identified in which HIS3 sequences were amplified. Two types of tandem duplications of the GAL(7, 10, 1) locus were also directed, and one type was not observed in rad52 mutants. Recombination mechanisms are discussed to account for these differences.